Development of a School-Based Intervention to Increase Physical Activity Levels Among Chinese Children: A Systematic Iterative Process Based on Behavior Change Wheel and Theoretical Domains Framework - Wang, Haiquan; Blake, Holly; Chattopadhyay, Kaushik (Frontiers in Public Health, 2021)
Regular physical activity has a range of benefits for children's health, academic achievement, and behavioral development, yet they face barriers to participation. The aim of the study was to systematically develop an intervention for improving Chinese children's physical activity participation, using the Behavior Change Wheel (BCW) and Theoretical Domains Framework (TDF). The BCW and TDF were used to (i) understand the behavior (through literature review), (ii) identify intervention options (through the TDF-intervention function mapping table), (iii) select content and implementation options [through behavior change technique (BCT) taxonomy and literature review], and (iv) finalize the intervention content (through expert consultation, patient and public involvement and engagement, and piloting). A systematic iterative process was followed to design the intervention by following the steps recommended by the BCW. This systematic process identified 10 relevant TDF domains to encourage engagement in physical activity among Chinese children: knowledge, memory, attention and decision processes, social influences, environmental context and resources, beliefs about capabilities, beliefs about consequences, social/professional role and identity, emotions, and physical skills. It resulted in the selection of seven intervention functions (education, persuasion, environmental restricting, modeling, enablement, training, and incentivization) and 21 BCTs in the program, delivered over a period of 16 weeks. The BCW and TDF allowed an in-depth consideration of the physical activity behavior among Chinese children and provided a systematic framework for developing the intervention. A feasibility study is now being undertaken to determine its acceptability and utility.